Projection of Tourist Climate Comfort Level Period 2031-2050 in Caldera Toba Geopark - Siregar, Alfonsius Chrisandy Pratama; Frida, Erna; Sinambela, Marzuki; Situmorang, Marhaposan; Humaidi, Syahrul; Darmawan, Yahya (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Tourism is one of the economic sectors that is developing relatively rapidly and has the potential to become a source of foreign exchange due to an increase in the number of tourists. Caldera Toba Geopark is one of the UNESCO-owned Geoparks in Indonesia as a tourist destination that depends on natural potential to be vulnerable to climate change. The relationship between climate and tourism from the comfort index is needed in determining tourist comfort. Climate parameters that become the calculation of the climate comfort index such as air temperature, rainfall, wind speed, length of sunshine and cloud cover are part of the thermal, physical and aesthetic aspects of climate comfort weighting. Climate projection data in this study is the RCP 4.5 scenario with the ACCESS 1-3 model. Using the TCI and HCI methods, the results of the temporal pattern analysis on the climate comfort index for the period 2031-2050 have a ’Bimodal - Shoulder Peak’ distribution pattern. Based on the results of the spatial pattern analysis, the level of tourist climate comfort for the period 2031-2050 both with TCI and HCI methods is dominated by the comfortable category index where the peak comfort occurs in December with a very comfortable category. The lowest comfort level with the TCI method occurs in June in the comfortable category, while the HCI method in July with a comfortable category. In the end, the results of this study provide recommendations for the best tourist time in the Caldera Toba Geopark from September to December. The recommended geosite locations are Simanindo - Batu Hoda and Hutatinggi - Sidihoni geosites.